Kajian Literatur: Implementasi PSAK 116 (IFRS 16) Sewa dan Praktik Manajemen Laba - Desvina Mayang Kinanti; Liza Alvia (International Forum of Researchers and Lecturers, 2025)
The implementation of Financial Accounting Standards Statement (PSAK) 116, which replaces PSAK 30, aims to enhance financial statement transparency by eliminating off-balance sheet transactions. This study reviews the literature on the impact of PSAK 116 on earnings management practices. The literature review findings reveal differing results across studies; some indicate that PSAK 116 improves transparency and reduces earnings management, while others suggest that PSAK 116 instead encourages earnings management to maintain certain financial ratios. Factors such as firm size, industry sector, regulatory environment, and corporate governance influence how PSAK 116 affects managerial behavior. The implications of this study highlight the importance of oversight and additional regulations to minimize the likelihood of financial statement manipulation, as well as the need for further research to understand the impact of PSAK 116 across various industry contexts and business environments.